Coexistence of informal hybrid space in the development of Jatinegara station area in East Jakarta - Endangsih, Tri; Hakim (Program Studi Arsitektur Fakultas Teknik Universitas Katolik Widya Mandira, 2024)
The phenomenon of rapid increase in urban population has triggered spatial densification. By taking a densely populated area in the Jatinegara station transit area, this research tries to explore the typology of density patterns in residential areas and public buildings. The use of space and the spatial pattern of cohabitation between the informal sector and urban space are investigated in this study. Participatory design, space syntax simulation, and space use pattern observation are the methods employed in this study to address the case. The findings indicate that inserting, pasting, and stretching are the three types of compactions. Settlements, public buildings, and pedestrian spaces all experience hybrid forms of compaction. The results demonstrate that the cohabitation of hybrid spaces is negotiated, and spatial, and results in synergistic governance. The three categories of hybrid coexisting spaces are defined as informal places that coexist with formal spaces through hybridization. From the results of spatial observation and perception mapping in the process of densification, the research produced recommendations in a guided participatory workshop. This research is expected to contribute to the concept of overcoming architectural design problems of density in framing public space.